Implementasi Sistem Informasi Triase IGD Pasien Rawat Jalan di Rumah Sakit X - Nawawi, Azhar; Sufyana, Candra Mecca; Gunawan, Erix (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Technology played an important role during the industrial revolution to help increase human activity and workforce in hospitals, in the emergency department triage installations were not yet computerized. There were problems found in the emergency department, there were incomplete triage entries and there were delays in the triage reporting process. With this, an information system is needed to improve the performance of nurses and doctors in making triage so that it is fast, complete and accurate. This research includes observation, interviews, and literature study with qualitative analysis. This program was created using the Black Box Testing method. This design produces an information system using methods that are able to assist the performance of nurses and doctors in making triage so that the reporting process carried out by officers produces accurate data. So, information systems are able to integrate services for increasing patients in hospitals.